2018
DOI: 10.1371/journal.pntd.0006391
|View full text |Cite
|
Sign up to set email alerts
|

A holistic approach to the mycetoma management

Abstract: Mycetoma, one of the badly neglected tropical diseases, it is a localised chronic granulomatous inflammatory disease characterised by painless subcutaneous mass and formation of multiple sinuses that produce purulent discharge and grains. If untreated early and appropriately, it usually spread to affect the deep structures and bone resulting in massive damage, deformities and disabilities. It can also spread via the lymphatics and blood leading to distant secondary satellites associated with high morbidity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 70 publications
(76 citation statements)
references
References 40 publications
1
54
0
Order By: Relevance
“…Due to general lack of or inaccessibility to pathological services across the country, it is also possible that many patients were clinically diagnosed with mycetoma and were/are managed empirically on a combination of antifungal and antibacterial agents. Experience from Sudan has shown that establishing a centre of excellence for mycetoma improved active case findings, diagnosis and management of the disease [21]. Mycetoma Research Centre in Sudan alone cares for over 8,800 patients, a value slightly higher than the earlier global estimate of the burden of mycetoma [5].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 96%
“…Due to general lack of or inaccessibility to pathological services across the country, it is also possible that many patients were clinically diagnosed with mycetoma and were/are managed empirically on a combination of antifungal and antibacterial agents. Experience from Sudan has shown that establishing a centre of excellence for mycetoma improved active case findings, diagnosis and management of the disease [21]. Mycetoma Research Centre in Sudan alone cares for over 8,800 patients, a value slightly higher than the earlier global estimate of the burden of mycetoma [5].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 96%
“…To overcome this, early case detection, which depends on detecting the visual warning signs of the disease and treatment is the only available means to prevent the numerous and serious complications of mycetoma. The first step in early case detection is meticulous clinical examination of the suspected patients, as other diagnostics tools, including direct microscopy, culture, histopathology and molecular identification, are commonly not available in mycetoma- endemic regions [ 60 ].…”
Section: The Differential Diagnosismentioning
confidence: 99%
“…Antibiotics and antifungals effective in the treatment of mycetoma are included in the WHO Model List of Essential Medicines [20], but the long duration of treatment [8] and monitoring [16] means they may be prohibitively expensive [2]. In Sudan, for example, treatment with itraconazole can cost US$26 per day [21]. Thus, there is a clear need for new, effective diagnostics and treatments, accessible to those who need it; simple yet innovative approaches could prove fruitful [5] (for example, staining mycetoma grains with henna for histological analysis [12]).…”
Section: Introductionmentioning
confidence: 99%